2022
DOI: 10.1111/jth.15836
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐GPVI nanobody blocks collagen‐ and atherosclerotic plaque–induced GPVI clustering, signaling, and thrombus formation

Abstract: Background:The collagen receptor glycoprotein VI (GPVI) is an attractive antiplatelet target due to its critical role in thrombosis but minor involvement in hemostasis.Objective: To investigate GPVI receptor involvement in platelet activation by collagen-I and atherosclerotic plaque using novel blocking and non-blocking anti-GPVI nanobodies (Nbs).Methods: Nb effects on GPVI-mediated signaling and function were assessed by western blot and whole blood thrombus formation under flow. GPVI clustering was visualize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 52 publications
(181 reference statements)
0
7
0
Order By: Relevance
“…39 After labeling, the nanobody appeared to be suitable for the imaging of platelet GPVI clusters. 49 After whole-blood perfusion over collagen-H, we observed that the adhered platelets showed a high Nb28-AF488 signal. The AF488 fluorescence was concentrated at contact sites of the platelets with collagen ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…39 After labeling, the nanobody appeared to be suitable for the imaging of platelet GPVI clusters. 49 After whole-blood perfusion over collagen-H, we observed that the adhered platelets showed a high Nb28-AF488 signal. The AF488 fluorescence was concentrated at contact sites of the platelets with collagen ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The isolation of plaque material from carotid endarterectomy and the homogenisation process, may affect the structural arrangement of the different extracellular matrix proteins, altering the function compared to the atherosclerotic lesion in situ . A lack of fibrillar collagen has been reported in homogenates [ 49 ], which may in part explain recent findings demonstrating differential GPVI activation on fibrillar collagen compared to plaque homogenate [ 48 , 52 ]. Our own studies, however, have also demonstrated a significant difference in thrombus formation on Type 1 Horm collagen compared to native extracellular matrix proteins produced by human coronary artery endothelial cells (Drysdale and Jones, unpublished data).…”
Section: Plaque Components and Cell Derived Matricesmentioning
confidence: 96%
“…Inhibition of α2β1, however, was without effects. 67–70 Notably, plaque composition and structure are not taken into account in these experimental set-ups.…”
Section: Platelet Response To Plaque Phenotype and Consequences For C...mentioning
confidence: 99%